[A Dangerous life ; Life line ; Musikahan sa Probe [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
The death of fashion designer Caloy Badidoy made the gay community very careful about their active night life. A look at training paramedics in the Philippines composed of doctors and lay people on rescue operations, first aid or life saving techniques. An interview with Ryan Cayabyab about his music career.